Dynamics of productivity growth in Indian dairy products manufacturing industry - KUMAR, SHIV; ABDULLA, ABDULLA (The Indian Journal of Animal Sciences, 2021)
The study assesses the total factor productivity of dairy products manufacturing industry of the year 2009–13 using stochastic frontier production approach. The study concludes that the change in total value of output of industry is due to adoption of efficient and best practices by processors. The TFP growth of dairy industry is 4.3% mainly driven by technical change over time. Temporarily, the dairy industry is moving towards overcoming the constraints in TFP growth. There is more need to augment capital which is energy efficient and accordingly capacity building of emerging skill sets in the industry.